Repeated large‐magnitude earthquakes in a tectonically active, low‐strain continental interior: The northern Tien Shan, Kyrgyzstan. Issue 5 (19th May 2016) - Landgraf, A.; Dzhumabaeva, A.; Abdrakhmatov, K. E.; Strecker, M. R.; Macaulay, E. A.; Arrowsmith, JR.; Sudhaus, H.; Preusser, F.; Rugel, G.; Merchel, S.
Abstract: The northern Tien Shan of Kyrgyzstan and Kazakhstan has been affected by a series of major earthquakes in the late 19th and early 20th centuries. To assess the significance of such a pulse of strain release in a continental interior, it is important to analyze and quantify strain release over multiple time scales. We have undertaken paleoseismological investigations at two geomorphically distinct sites (Panfilovkoe and Rot Front) near the Kyrgyz capital Bishkek. Although located near the historic epicenters, both sites were not affected by these earthquakes. Trenching was accompanied by dating stratigraphy and offset surfaces using luminescence, radiocarbon, and 10 Be terrestrial cosmogenic nuclide methods. At Rot Front, trenching of a small scarp did not reveal evidence for surface rupture during the last 5000 years. The scarp rather resembles an extensive debris‐flow lobe. At Panfilovkoe, we estimate a Late Pleistocene minimum slip rate of 0.2 ± 0.1 mm/a, averaged over at least two, probably three earthquake cycles. Dip‐slip reverse motion along segmented, moderately steep faults resulted in hanging wall collapse scarps during different events. The most recent earthquake occurred around 3.6 ± 1.3 kyr ago (1 σ ), with dip‐slip offsets between 1.2 and 1.4 m. We calculate a probabilistic paleomagnitude to be between 6.7 and 7.2, which is in agreement with regional data from the Kyrgyz range. The morphotectonic signals in the northern Tien Shan are a prime example of deformation in a tectonically active intracontinental mountain belt and as such can help understand the longer‐term coevolution of topography and seismogenic processes in similar structural settings worldwide. Key Points: Repeated M 7 earthquakes along the Tien Shan mountain front near historic seismic cluster Segmented instead of full‐length ruptures along the mountain front Episodic faulting and superposed geomorphic processes in low‐strain mountain belt